The Learning Model Use ; Think, Pair, Share in Improving Collaborative Ability and Student Representation - Sukarya Zaenal Arifin Zaenal (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2020)
Background: The research aims to find out the learning model use ; think, pair, share in improving collaborative ability and student representation of human motion system material in grade XI SMAN 4 Bandung. Method: This study is a class action study, which involves 30 students from XI MIPA 6 at sman 4 bandung. The research instruments used observation sheet to measure collaborative ability and representation, and secondary instruments like cognitive tests of multiple choice, student response numbers, and teacher activity observation sheets. Results: The role of learning model Think, pair, share in improving student colaborative activity increased in cycles I and cycle II with 5 aspects of collaborative ability ; contributions, time management, problem solving, working with others, and investigative techniques. The role of learning model Think, pair, share in improving student representation ability increased in cycle I and II, with 3 aspects of represetation ability ; legibility, depth of material, effectiveness. Conclusion: Meanwhile the result shows most of teachers have been run the steps of think, pair, share and the process occured improvement in every cycle.